PepBio: predicting the bioactivity of host defense peptides - Saw Simeon; Hao Li; Thet Su Win; Aijaz Ahmad Malik; Abdul Hafeez Kandhro; Theeraphon Piacham; Watshara Shoombuatong; Pornlada Nuchnoi; Jarl E. S. Wikberg; M. Paul Gleeson; Chanin Nantasenamat (My University, 2017)
A large-scale QSAR study of host defense peptides sheds light on the origin of their bioactivities (antibacterial, anticancer, antiviral and antifungal).
Keywords: Antibacterial peptide; Antimicrobial Peptides and Activities